2018
DOI: 10.13106/jafeb.2018.vol5.no4.67
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Management Disclosure and Analysis on the Stock Crash Risk: Evidence from Korea

Abstract: The purpose of this study is to investigate the effect of quality of management discussion and analysis (MD&A) disclosure on stock price crash risk. The MD&A can be seen to reflect the management's intention on public announcement and reveals directly what the management says to communicate with outside investors. A firm's high-quality MD&A implies the management's commitment to communicating with the market, not allowing the managers to have incentives to hoard unfavorable news, which if revealed to the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Research has shown that corporate information disclosure plays an important role in minimizing information asymmetry and reducing agency problems (Cormier, Ledoux, & Magnan, 2011). In particular, the publication of information, both mandatory and voluntary for the capital market, will help companies to reduce capital costs, gain investor confidence, and increase the value of the stock market (Mahadeo et al, 2011), (Baimukhamedova, Baimukhamedova, & Luchaninova, 2017;Lee & Chae, 2018). Hardiningsih, Januarti, Yuyetta, Srimindarti, and Udin (2020), Perrini, Russo, Tencati, and Vurro (2011) conclude that revealing more information and thus reducing asymmetric information can reduce the cost of the company capital.…”
Section: Agency Theorymentioning
confidence: 99%
“…Research has shown that corporate information disclosure plays an important role in minimizing information asymmetry and reducing agency problems (Cormier, Ledoux, & Magnan, 2011). In particular, the publication of information, both mandatory and voluntary for the capital market, will help companies to reduce capital costs, gain investor confidence, and increase the value of the stock market (Mahadeo et al, 2011), (Baimukhamedova, Baimukhamedova, & Luchaninova, 2017;Lee & Chae, 2018). Hardiningsih, Januarti, Yuyetta, Srimindarti, and Udin (2020), Perrini, Russo, Tencati, and Vurro (2011) conclude that revealing more information and thus reducing asymmetric information can reduce the cost of the company capital.…”
Section: Agency Theorymentioning
confidence: 99%
“…The bulk of recent empirical studies on crash risk follows the agency theoretical concept of Jin and Myers (2006) who show that information asymmetry between managers and investors contributes to crash risk (e.g., Hutton et al, 2009;Lee & Chae, 2018;Chae, Nakano, & Fujitani, 2020). Information asymmetry allows managers to delay bad news over time to protect employment and maximize compensation (Kothari, Shu, & Wysocki, 2009).…”
Section: Stock Price Crash Riskmentioning
confidence: 99%
“…Lee and Chae [10] use logistic regression to test whether MD&A influences crash risk using listed companies in the Korean Stock Exchange (KSE) stock market, which indicates that a firm's high-quality MD&A implies the management's commitment to communicating with the market, not allowing the managers to have incentives to hoard negative news. Thus, the high-quality MD&A is likely to reduce the stock price crash risk.…”
Section: The Effect Of Quality Of Management Discussion and Analysis (Mdanda) Disclosure On Stock Price Crash Riskmentioning
confidence: 99%